Reception of QS. Al-Baqarah: 188 and An-Nisa: 29 Regarding Unauthorized Use of Others' Belongings Among Mahasantri at Ma'had Al-Jami'ah IAIN Kendari: Resepsi Mahasantri atas Qs. Al-Baqarah:188 And Qs. An-Nisa:29 (Studi Kasus Penggunaan Barang Orang Lain Tanpa Izin) - Siti Hotiza; Ni’matuz Zuhrah; Danial Danial (Takwil: Journal of Quran and Hadith Studies, 2025)
The behavior of using other people's belongings without permission among Ma'had Al-Jami'ah IAIN Kendari mahasantri is an important concern in maintaining social ethics and morality. This study aims to understand the factors that influence this behavior, with a focus on the reception of QS. Al-Baqarah verse 188 and QS. An-Nisā verse 29. The research method used is qualitative through field studies, which involve observation and interviews with mahasantri. The results show that 33.33% of mahasantri engage in this behavior, with patterns of action such as using items and then returning them, or even not returning them at all. The contributing factors include lack of awareness, urgent circumstances, and bad habits. Although the majority of mahasantri understand that this action is prohibited by these verses, a small number believe that it can be justified in certain situations. The impact includes positive changes in social interactions, with increased awareness of the importance of respecting the property rights of others and collective efforts to prevent violations. This study emphasizes the need for further education on the ethics of using items and the more effective application of the teachings of the Qur'an in daily life. Thus, a deeper understanding of this prohibition can contribute to the formation of a better character of respecting the property rights of others among mahasantri.